Bioinformatics Applications Based On Machine Learning - Chamoso, Pablo; Rodriguez, Sara; Mohamad, Mohd; González-Briones, Alfonso (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The great advances in information technology (IT) have implications for many sectors, such as bioinformatics, and has considerably increased their possibilities. This book presents a collection of 11 original research papers, all of them related to the application of IT-related techniques within the bioinformatics sector: from new applications created from the adaptation and application of existing techniques to the creation of new methodologies to solve existing problems.